Commercial versus Legal Approaches: Alternative Strategies to Resolving Third- Party IPR Issues Confronting New Ventures - Hartwell, Ian P.; Molian, David (Cranfield University, 2009)
For many technology-based ventures, whether classic start-ups or corporate ventures, the viability of the business rests on intellectual property rights (IPR). The costs of registering and protecting IPR are well documented and often present a significant obstacle for entrepreneurs to overcome. In addition to these are the costs of inappropriate forms of due diligence, often involving IPR investigation, evidenced in the work of Molian and Solt (2002). "Conventional" due diligence outcomes involving IPR can create a limited set of options leading to the abandonment of a promising opportunity, where IPR - in particular patents - owned by a third-party are seen as the major stumbling-block. In this paper the authors present alternative, "commercial" approaches to dealing with the issues of third-party IPR ownership, which can circumvent the original problem. Unfortunately such strategies are often not considered by advisers. The approaches examined are based on examples drawn from the automotive industry, but the authors argue that both principles and application have wider relevance across industry and in particular to resource-constrained start-up businesses.